PENGARUH PENERAPAN MEDIA FLASHCARD BERBASIS EDUCARE TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS V SPF SD INPRES PANAIKAN II/I KOTA MAKASSAR : - - Nurwana; Hamzah Pagarra; Siti Raihan (STKIP Subang, 2026)
This study aimed to determine the implementation of Educare-based flashcard media, to describe the learning independence of fifth-grade students, and to examine the effect of using Educare-based flashcard media on the learning independence of fifth-grade students at UPT SPF SD Inpres Panaikang II/I, Makassar City. This study employed a quantitative approach using a quasi-experimental design with a Nonequivalent Control Group Design. The sample consisted of 67 students, including 32 students in the experimental class and 35 students in the control class. Data were collected using a learning independence questionnaire and observation sheets. The data were analyzed using descriptive and inferential statistics with the assistance of IBM SPSS Statistics. The results indicated that the implementation of Educare-based flashcard media was categorized as very good, with an implementation percentage of 82.5% by the teacher and 78% by the students. The learning independence of students in the experimental class was categorized as very high after receiving the treatment. The hypothesis testing results showed a significance value of p < 0.05, indicating that H₁ was accepted and H₀ was rejected. It can be concluded that the use of Educare-based flashcard media has a positive and significant effect on the learning independence of fifth-grade students at UPT SPF SD Inpres Panaikang II/I, Makassar City